just subtract 4 from -4
answer: it dropped 55%
step-by-step explanation: well if you multiply 140x.55 it equals to 77
5. y = -3x -2
7. k = (dw -grp)/l
9. t = j + l - t
10. b = df - a - c
in each case, the steps are the same:subtract every term that does not contain the variable of interest.divide by the coefficient of the variable of interest.simplify as needed.
5. the variable of interest (y) is on the left side of the equation. the other term there is -3x, so we add 3x (same as subtract -3x) to both sides of the equation:
-4y = 12x + 8
now, we divide both sides by -4.
y = -3x -2
7. the term not containing k on the left side of the equation is dw/g, so we subtract that from both sides of the equation.
-kl/g = rp -dw/g
now, we multiply the equation by the inverse of the coefficient of k, which is -g/l:
k = (-g/l)·rp /l)·(dw/g) = -grp/l +dw/l
k = (dw -grp)/l
in this case, it can be a little easier if you multiply by g first, then subtract dw and divide by -l. the end point is the same, but the route is slightly different.
9. terms not containing t are p and -l. subtracting those from both sides of the equation gives
t = j +l -t
10. subtracting terms a and c from both sides of the equation gives
b = df -a -c